“PERAN PANCASILA PADA ERA GLOBALISASI” KAJIAN TERHADAP PANCASILA DAN FENOMENA LGBT (LESBIAN,GAY,BISEXUAL,TRANSGENDER) DI INDONESIA - Wawan Setiawan; Yudhitiya Dyah Sukmadewi (Jurnal Dinamika Sosial Budaya, 2017)
LGBT phenomenon into a "hot issue" in the international and national levels. LGBT phenomenon in Indonesia would result in the pros and cons of the community. Various groups of people, mainly from religious groups opposed to the existence of the phenomenon. On the other hand, there are also groups that support the LGBT community in Indonesia, the main actors and human rights activists (Human Rights). Most LGBT people found contrary to the noble values of Pancasila, but on the other hand assumes that actors LGBT community is not sexual deviation, and shall have the rights and equality. It is thus necessary to do a study to determine the response of the people of Indonesia respond to the phenomenon of LGBT specifically in this case the younger generation, as well as to determine whether or not the phenomenon of LGBT contrary to the basic values of Pancasila as the State Indonesia.